An assessment of football referees' decisions in incidents leading to player injuries - Fuller, C. W.; Junge, A.; Dvorak, J. (The American Journal of Sports Medicine, 2004)
PURPOSE: To assess whether match injuries to footballers occurred as a result of players' noncompliance with the rules of the game, match referees could reliably identify the legality of incidents leading to injury, and the rules of football were adequate to protect players from injury. METHODS: Video recordings of incidents leading to injury in 12 FIFA tournaments were used to identify parameters. Team physicians reported the details of match injuries. Two panels of FIFA referees reassessed the legality of incidents from these tournaments that resulted in injuries. RESULTS: In total, 148 general injuries and 84 head/neck injuries were assessed. For the general injuries, the match referees identified 47% and the referees' panel identified 69% as fouls. For head injuries, the match referees identified 40% and the referees' panel identified 49% as fouls. CONCLUSIONS: Decisions made on the legality of tackles leading to injury indicated that the current rules of football were adequate for the majority of tackle situations, although the reliability with which referees could identify fouls during some match conditions was low. For incidents leading to head/neck injuries, the match referees and the referees' panel both identified a smaller proportion of injury situations as fouls.